Hepatitis B Virus Serological Markers in a Rural Community in Southeastern Nigeria (2017)
Due to the current blood safety algorithm in Nigeria which excludes only Hepatitis B surface Antigenaemia (HBsAg) positive individuals from blood donation, this study was therefore designed to investigate HBV markers of infection in a rural population in southeastern Nigeria. It is a cross sectional community-based study. This study was carried out in Awuda village in Nnobi town of southeastern Nigeria in August 2013. A total of 92 consenting participants were enrolled for the study. The participants were screened for HBsAg, HBeAg, Anti-HBc IgM, Anti-HBc, Anti-HBe and Anti-HBs using ELISA technique and classified into different serological profiles indicative of infection stages. Respondents’ mean age was 26.3(SD +11.5) years and 58 of them were females while 34 were males. An overall prevalence for HBsAg was 1.1% (1/92). The same HBsAg positive individual also had detectable anti-HBe and anti- HBc IgM. Analysis of the results showed 3 (3.3%) of the study participants were positive for both Anti-HBe and Anti-HBc. Also, 12 (13.0%) participants were positive for only Anti-HBc and Anti-HBs antibody. Another 9 (9.8%) participants were positive for only Anti-HBs while 51 (55.0%) had no serological marker for previous exposure to either HBV or HBV vaccine. Altogether, 31(33.7%), 1(1.1%) and 21(22.8%) participants were positive for HBc, HbcIgM and HBs antibodies respectively. This study has demonstrated that at least 1 out of every 3 people in the studied community might have serological evidence of present or past HBV infection. The current dependence of blood safety algorithms which excludes only HBsAg positive individuals is not enough to guarantee safety of blood and/or blood products. More studies are needed to further investigate the theoretical basis of the algorithm.